Empowering East African armers with weather and climate information services: ECREA's climate-smart strategies for resilient agriculture in the bean value chain - Kiogora, Joseline; Kagabo, Desire; Byandaga, Livingstone; Mvuyibwami, Patrick; Ngige, Chris (2024)
In the face of escalating climate crisis and its profound impact on small-scale agricultural producers in Sub-Saharan Africa (SSA), initiatives such as the Enhancing Climate Change Resilience in East Africa (ECREA) project emerge as beacons of hope. The ECREA project is spearheaded by the Climate Action lever of the Alliance of Bioversity International and CIAT through the Pan-Africa Bean Research Alliance (PABRA), with the goal of upscaling the provision of Weather and Climate Information Services (WCIS) to bean value chain actors in East Africa. ECREA - funded by the UK Government's Foreign, Commonwealth and Development Office (FCDO) - is a concerted effort to address the pressing challenges exacerbated by shifting weather patterns.